Detecting High-Resolution Intramural Vascular Wall Strain Signals Using DICOM Data. Issue 3 (March 2022) - Weitzel, William F.; Thelen, Brian J.; Rajaram, Nirmala; Gao, Jing; Hamilton, James; Morgan, Timothy; Zheng, Yihao; Funes-Lora, Miguel Angel; Krishnamurthy, Venkataramu N.; Osborne, Nicholas; Henke, Peter; Bishop, Brandie; et al.
Abstract : Maintaining dialysis vascular access is a source of considerable morbidity in patients with end-stage renal disease (ESRD). High-resolution radiofrequency (RF) ultrasound vascular strain imaging has been applied experimentally in the vascular access setting to assist in diagnosis and management. Unfortunately, high-resolution RF data are not routinely accessible to clinicians. In contrast, the standard DICOM formatted B-mode ultrasound data are widely accessible. However, B-mode, representing the envelope of the RF signal, is of much lower resolution. If strain imaging could use open-source B-mode data, these imaging techniques could be more broadly investigated. We conducted experiments to detect wall strain signals with submillimeter tracking resolutions ranging from 0.2 mm (3 pixels) to 0.65 mm (10 pixels) using DICOM B-mode data. We compared this submillimeter tracking to the overall vascular distensibility as the reference measurements to see if high-strain resolution strain could be detected using open-source B-Mode data. We measured the best-fit coefficient of determination between signals, expressed as the percentage of strain waveforms that exhibited a correlation with a p value of 0.05 or less. The lowest percentage was 86.7%, and most were 90% and higher. This indicates high-resolution strain signals can be detected within the vessel wall using B-mode DICOM data.